Constructing the Infrastructure for the Knowledge Economy Methods and Tools, Theory and Practice - Linger, Henry; Fisher, Julie; Wojtkowski, W. Gregory; Wojtkowski, Wita (Springer US, 2004)
Constructing the Infrastructure for the Knowledge Economy: Methods and Tools, Theory and Practice is the proceedings of the 12th International Conference on Information Systems Development, held in Melbourne, Australia, August 29-31, 2003. The purpose of these proceedings is to provide a forum for research and practice addressing current issues associated with Information Systems Development (ISD). ISD is undergoing dramatic transformation; every day, new technologies, applications, and methods raise the standards for the quality of systems expected by organizations as well as end users. All are becoming more dependent on the systems reliability, scalability, and performance. Thus, it is crucial to exchange ideas and experiences, and to stimulate exploration of new solutions. This proceedings provides a forum for just that, addressing both technical and organizational issues